Business and Administrative Communication - Locker Kitty O (MC Graw Hill, 2004)
This Seventh Edition of Business and Administrative Communication by Kitty Locker is a true leader in the business communications field. Beyond covering the broad scope of topics in both oral and written business communication, Locker’s text uses a student-friendly writing style and strong design element to hold student attention. Real-world examples and real business applications underscore the relevance and importance of the material presented to the classroom experience and to the students’ careers. Kitty Locker’s text also conveys the best possible advice to students through its research base; the author’s reputation as a contributor to this field of study lends an even greater element of teachability and relevance to this market-leading title. Locker continues to lead the pack with innovative technology offerings – the BComm Skill Booster, PowerWeb – round out the learning experience with Business and Administrative Communication